The External Diffusion of Galician and the Galician Diaspora - Kakihara, Takeshi (Madrygal. Revista de Estudios Gallegos, 2019)
The purpuse of this study is to get closer to the reality of the policy of external diffusion of the Galician language by the Xunta de Galicia and to clarify its meaning and its relations with the Galician emigrants and their descendants. The Xunta de Galicia has been carrying out activities to spread Galician as part of the policy of linguistic normalization. It is assumed that the following two are the main activities for the diffusion of this language: (1) the promotion of Galician for non-Galician speakers and (2) the maintenance of the language for the Galician emigrants. The author of this study presents in this article what kind of measures each party involved have realized taking into account the data obtained from the bibliographical consultation and the interviews with the parties involved: the Secretaría Xeral da Política Lingüística, the Secretaría Xeral da Emigración, the Centros galegos and the Instituto Cervantes. In this article we will analyze the cases of Argentina, Brazil and Germany as examples of the countries to where many Galicians emigrated. We will also analyze the activities developed by the Centers of the Instituto Cervantes in relation to the diffusion of the co-official languages of Spain.
Keywords: Galician Language Diffusion Policy; Centros Galegos; Galician Diaspora; Linguistic Policy